Faculty, staff, and student perceptions of substance use disorder stigma in health profession training programs: a quantitative study - Rachel E. Barenie; Alina Cernasev; R. Eric Heidel; Steven Stewart; Kenneth Hohmeier (BMC, 2023)
Abstract Background Research indicates that stigma impacts the care provided to individuals with Substance Use Disorders (SUDs), but perceptions of SUDs in various healthcare training programs are not well known. We aimed to characterize perceptions of faculty, staff, and students about SUD stigma in professional healthcare training programs. Methods We conducted a cross-sectional survey of faculty, staff, and students employed at or enrolled in one of six health-related colleges at one Mid-South health science center in the United States, including medicine, pharmacy, dentistry, nursing, health professions, and graduate health sciences. Data collection occurred between February and March 2021. We used descriptive and frequency statistics to assess the constructs within the survey instrument. Results A total of 572 respondents participated in this study (response rate = 9%; students, n = 428, 75%; faculty, n = 107, 19%; staff, n = 32, 6%). Most respondents reported interacting with persons with a SUD, cited challenges with the interaction, and perceived SUDs to be mental health condition (n = 463) or biological disease (n = 326). Most respondents believed that their college: emphasizes learning about SUDs; promotes an accurate perception of SUDs; and fosters respect for persons with. Few respondents reported they hear faculty, staff, or students express negative comments about persons with SUDs, but they were sometimes expressed by students. Conclusions Most faculty, staff, and students reported experiencing challenges when interacting with a person with a SUD, mainly communication, but few recalled hearing negative comments from their peers. Whether interventions tailored towards improving communication in academic healthcare training settings could minimize challenges experience by faculty, staff, and students when serving individuals with SUDs should be further evaluated.